Problems of the Starting and Operating of Hydraulic Components and Systems in Low Ambient Temperature (Part IV) - Jasiński Ryszard (Polish Maritime Research, 2017)
Designers of hydraulically driven machines and devices are obliged to ensure during design process their high service life with taking into account their operational conditions. Some of the machines may be started in low ambient temperature and even in thermal shock conditions (due to delivering hot working medium to cold components). In order to put such devices into operation appropriate investigations, including experimental ones - usually very expensive and time-consuming, are carried out. For this reason numerical calculations can be used to determine serviceability of a hydraulic component or system operating in thermal shock conditions. Application of numerical calculation methods is much less expensive in comparison to experimental ones. This paper presents a numerical calculation method which makes it possible to solve issues of heat exchange in elements of investigated hydraulic components by using finite elements method. For performing the simulations the following data are necessary: ambient temperature, oil temperature, heat transfer coefficient between oil and surfaces of elements, as well as areas of surfaces being in contact with oil. By means of computer simulation method values of clearance between cooperating elements as well as ranges of parameters of correct and incorrect operation of hydraulic components have been determined. In this paper results of computer simulation of some experimentally tested hydraulic components such as axial piston pump and proportional spool valve, are presented. The computer simulation results were compared with the experimental ones and high conformity was obtained.